THE ROLE OF FATHER INVOLVEMENT IN BUILDING ADOLESCENT MENTAL HEALTH - Sari, Putri Puspita; Hanifah, Rulia; Dewi, Rini Liana; Riady, Muhammad Antos (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2025)
Abstract Fathers' involvement is often overlooked in the parenting discourse, despite its important role in shaping adolescents' mental health. However, related studies are scattered and have not been systematically reviewed. This review aims to examine fathers' involvement in parenting, the dimensions of involvement, its impact on adolescents' mental health, and factors that may moderate the relationship. This study is a Systematic literature review that follows the PRISMA 2020 guidelines. Articles were searched through PsycINFO, PubMed, Springer, Ebsco, Google Scholar, and Scopus databases using keywords such as